Extramammary Paget’s Disease: A Case Report - Shah, Anita; Poudel, Yogesh; Poudel, Anuj (Journal of Universal College of Medical Sciences, 2020)
A 60- year-old man presented with four year history of a non- healing rash. The rash was pruritic and painless. He had previously been treated empirically with oral and topical antibiotics, topical antifungal agents, and topical glucocorticoids without improvement. The physical examination revealed an erythematous plaque with superficial white scale affecting the skin of the groin and scrotum. Skin biopsy and histopathology revealed epidermal infiltration by large atypical cells that had eosinophilic cytoplasm and prominent nucleoli, findings were consistent with Pagets disease. Extramammary Paget's disease (EMPD) is an intraepithelial adenocarcinoma that is sometimes misdiagnosed as dermatitis clinically. It most commonly involves the vulva and in perianal skin, scrotum, penis and axilla. The patient was kept on regular surveillance. The patient has increased intensity of itching and increase in size of lesion after six months of diagnosis.